Family violence in the elderly age - Delfín Rivera Dueñas, Max Marco (2008)
This article analyzes the recurrent problem in Family rights, in our society known as intra-family violence, the text begins with an introduction about time as a measure or work frame and its scientific conception, then talks about the age of the people, the effect and consequences of the pass of the time in human beings and its somatic aspect and the perception that we have about the elders. Finally analyzes what is happening in the cases where elders are involved in process of domestic violence and some suggestions about it.